(untitled) - Zarowski, Christopher J. (Hoboken, NJ., 2004)
To properly function in today’s work environment, engineers require a working familiarity with numerical analysis. This book provides that necessary background, striking a balance between analytical rigor and an applied approach focusing on methods particular to the solving of engineering problems
Keywords: Electric engineering,Computer science,Kỹ sư về điện; Mathematics,Mathematics,Toán học